The role of locomotion in psychological development - Anderson, David I.; Campos, Joseph J.; Witherington, David C.; Dahl, Audun; Rivera, Monica; He, Minxuan; Uchiyama, Ichiro; Barbu-Roth, Marianne (Frontiers in Psychology, 2013)
The psychological revolution that follows the onset of independent locomotion in the latter half of the infant’s first year provides one of the best illustrations of the intimate connection between action and psychological processes. In this paper, we document some of the dramatic changes in perception-action coupling, spatial cognition, memory, and social and emotional development that follow the acquisition of independent locomotion. We highlight the range of converging research operations that have been used to examine the relation between locomotor experience and psychological development, and we describe recent attempts to uncover the processes that underlie this relation. Finally, we address three important questions about the relation that have received scant attention in the research literature. These questions include: 1) What changes in the brain occur when infants acquire experience with locomotion? 2) What role does locomotion play in the maintenance of psychological function? 3) What implications do motor disabilities have for psychological development? Seeking the answers to these questions can provide rich insights into the relation between action and psychological processes and the general processes that underlie human development.